Smart Grid Systems Based Survey on Cyber Security Issues - R. Dorothy; Sasilatha Sasilatha (Institute of Advanced Engineering and Science, 2017)
The future power system will be an innovative administration of existing power grids, which is called smart grid. Above all, the application of advanced communication and computing tools is going to significantly improve the productivity and consistency of smart grid systems with renewable energy resources. Together with the topographies of the smart grid, cyber security appears as a serious concern since a huge number of automatic devices are linked through communication networks. Cyber attacks on those devices had a direct influence on the reliability of extensive infrastructure of the power system. In this survey, several published works related to smart grid system vulnerabilities, potential intentional attacks, and suggested countermeasures for these threats have been investigated.